Utilisation of an infant sweating thermal manikin to determine clo values for infant clothing: a comparison of predictive formulas. Issue 3 (2nd September 2021) - Golden, Joshua; Brown, Tanner; Domina, Tanya; Wroblewski, Susanne; Kumphai, Pimpawan
ABSTRACT: Baby clothing refers to a product category for infants and toddlers aged 0–36 months. For the babywear designer, consideration of the thermal insulation provided by the garment is key to creating well-performing infant apparel. However, the thermal insulation value provided by baby apparel items is not readily available to designers. This study examined clo values provided by babywear products using an infant sweating thermal manikin. Results indicated that intrinsic clo values can be predicted from BSAC (body surface area covered by clothing) or garment weight. The study also examined the reliability of previously proposed clo estimation formulas for infant products, and results suggest that some of these derived formulas can predict clo values for infants' clothing. This work could lead to an industry standard thermal insulation guide for babywear that informs parents about the appropriate clothing choices for safety and comfort.